Style adaptacji uczniów do szkoły. Inspiracje dla nauczycieli wczesnej edukacji - Anna Babicka-Wirkus (Problemy Wczesnej Edukacji)
The paper presents the issue of students adaptation to school life and shows its importance for the practice of early education teachers. In the text, school is defined as an institution which strives to subjugate the subjects operating within it while, paradoxically, giving them conditions for resisting the imposed rigours. While trying to deal with this complex reality, students have developed three main styles of adapting to its conditions. These include the following: insider, outsider, and subsider style. The first one is based on conformist actions. Outsiders engage in resistance behaviors which lead to their marginalization and even premature abandonment of the educational path. Subsiders are the ones who are able to resist and transform the dominant reality by acting in a space determined by the dominant culture while, at the same time, crossing the set boundaries.